PROTECTING TRADE SECRETS IN LITIGATION - THE IMPACT OF ARTICLE 9 OF THE EU TRADE SECRET DIRECTIVE ESPECIALLY ON FINNISH LAW - Rindell, Joanna (fi=Turun yliopisto|en=University of Turku|, 2016)
In November 2013 the European Commission issued the “Proposal for a Directive on the European Parliament and of the Council on the protection of undisclosed know-how and business information (trade secrets) against their unlawful acquisition, use and disclosure” (referred to as “TSD”). The TSD offers minimum harmonisation and aims at promoting sharing of knowledge, and the exploitation of innovations on the Internal Market. The European Parliament adopted the TSD on April 14, 2016 and the EU Member States will have two years to implement it. The TSD includes a harmonised definition of a trade secret that builds on the definition provided in Article 39 of the TRIPS Agreement. Moreover, it also ensures the freedom of expression and information and the protection of whistle-blowers. Appropriate means of actions and remedies against unlawful acquisition, use and disclosure of trade secrets are also included, such as provisional and pecuniary measures, injunctions and corrective measures or allocation of damages. This study examines the protection of trade secrets in the course of litigation regulated in Article 9 of the TSD. Currently, the protection of trade secrets within the EU is fragmented especially in this regard, which makes companies reluctant to resort to litigation when a trade secret has unlawfully been misappropriated or it is suspected that a trade secret is being misused. The regulations in Article 9 expand only to the hearing in court. Such protection is welcomed and a step in the right direction. However, in my study I have found that in order for the protection to be sufficient there is a need to further establish measures to protect trade secrets during the entire process, from the filing of the claim to the end when the judgement is given. Consequently, I also discuss different measures that could be used to strengthen the protection of trade secrets before the hearing in court, as evidence are gathered.